Assessing the impact of Information and Communication Technologies on the Portuguese hotel sector: an exploratory analysis with Data Envelopment Analysis - Cidália Maria Leal Paço; Juan Manuel Cepeda Pérez (Tourism & Management Studies)
The overall objective of this paper is to evaluate the impact of Information and Communication Technologies (ICT) on the efficiency of four- and five-star hotels in Portugal and to contribute to the identification of mechanisms that explain the relationship between ICT and efficiency within the hotel sector through Data Envelopment Analysis (DEA). Overall, based on research fundamentals and the results obtained, it can be said that the main research questions were answered and the objectives of the study were achieved. In response to research questions related to the use of ICT in the Portuguese hotel industry, the following uses were determined for hotels in the sample: defining efficient frontiers, identifying efficient and inefficient hotels, ranking hotels according to their efficiency and revealing areas of inefficient hotels that have to be improved to increase effectiveness (improvement targets). Moreover, this study illustrates not only the importance of ICT in achieving higher levels of efficiency but also discusses other specific issues which must be taken into account so that the benefits of ICT can be experienced. Specifically, it was found that the availability of ICT does not alone lead to optimum performance.